The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jvec.12259
|View full text |Cite
|
Sign up to set email alerts
|

Control of maleAedes albopictusSkuse (Diptera: Culicidae) using boric acid sugar bait and its impact on female fecundity and fertility

Abstract: Aedes albopictus (Skuse) is a serious threat to human health as a vector of arboviruses such as dengue, chikungunya (Lambrechts et al. 2010, Gubler 1998, and Zika (Wong et al. 2013). Adult Ae. albopictus are controlled primarily via ground and aerial ultra-low volume applications of insecticides. The chemical insecticides may potentially pollute the environment, and mosquito populations gradually develop resistance to them (Waits et al. 2017). The future for mosquito control requires safer and more effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For instance, oral ingestion of TSB incorporating boric acid (a gut toxin) reduced adult mosquito daily survival probability, host-seeking, blood-feeding rates, fecundity, and fertility in Ae. albopictus (Ali et al, 2006;Wang et al, 2017). Consistent with these studies, we found that females who ingested TSB had substantially shorter daily survival than individuals in the control group.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, oral ingestion of TSB incorporating boric acid (a gut toxin) reduced adult mosquito daily survival probability, host-seeking, blood-feeding rates, fecundity, and fertility in Ae. albopictus (Ali et al, 2006;Wang et al, 2017). Consistent with these studies, we found that females who ingested TSB had substantially shorter daily survival than individuals in the control group.…”
Section: Discussionsupporting
confidence: 88%
“…Later, the same results were reported with an even lower concentration of boric acid (0.1%) in TSB solution against Aedes mosquitoes after 10 days exposure in laboratory 4 . Thereafter, several studies were undertaken with boric acid and sugar solution against Aedes and Culex mosquitoes, and > 90% mortality was observed after 48 h exposure under controlled conditions 15, 30, 39, 40 . Although the majority of studies reported significantly high mortality rates of Aedes mosquitoes with boric acid, a few recent studies documented relatively less mortality (50–70%) 23, 24, 33 .…”
Section: Toxicants Used In Atsbmentioning
confidence: 60%
“…4 Thereafter, several studies were undertaken with boric acid and sugar solution against Aedes and Culex mosquitoes, and > 90% mortality was observed after 48 h exposure under controlled conditions. 15,30,39,40 Although the majority of studies reported significantly high mortality rates of Aedes mosquitoes with boric acid, a few recent studies documented relatively less mortality (50-70%). 23,24,33 Based on the proven efficacy of boric acid with sugar solutions, several field trials were undertaken both outdoors and indoors.…”
Section: Toxicants Used In Atsbmentioning
confidence: 99%
“…albopictus and Ae. aegypti to be used in ATSB in fields of Florida [ 23 , 25 ]. In Brazil, the guava juice-ASB, mango juice-ASB, and cupuacu juice-ASB have been used to investigate their attractant potential against Ae.…”
Section: Discussionmentioning
confidence: 99%